Effectiveness of roadside vegetated filter strips and swales at treating roadway runoff: a tutorial review. Issue 4 (9th March 2018) - Boger, Alex R.; Ahiablame, Laurent; Mosase, Esther; Beck, Dwayne
Abstract : Water leaving roadside ditches has the potential to affect the quality of downstream waters. Abstract : Water leaving roadside ditches has the potential to affect the quality of downstream waters. Vegetated filter strips (VFS's) and grassed swales (GS's) are often used to manage roadside ditches for water quality protection. This paper summarized field data from relevant studies to determine the efficiency of these two best management practices (BMPs) in removing nutrients and trace metals from roadside ditches, and discussed implications for downstream water quality, as well as driving factors that influence the performance of roadside VFS's and GS's. The literature examined shows that roadside VFS's and GS's are quite effective at reducing total suspended solids (TSS), while a mixed performance was reported for metal and nutrient removal. Based on the data, VFS's and GS's appear to be more effective at removing particulate-bound than dissolved pollutants.